2004
DOI: 10.1097/00001756-200412030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation to emotional words in depressed vs healthy subjects

Abstract: Depression involves either enhanced processing of negative stimuli or diminished processing of positive stimuli. We used functional magnetic resonance imaging to assess brain activation in depressed vs healthy participants. Fifteen participants diagnosed with major depressive disorder and 15 controls were scanned during a lexical decision task involving neutral, happy, sad, and threat-related words. For happy words, depressed subjects exhibited less activation than did controls to happy words in fronto-tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
83
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 19 publications
18
83
1
4
Order By: Relevance
“…In a recent first study combining the NAP task with ERP in MDD, it was also found that MDD participants had reduced central-parietal P2 amplitude for negative experimental trials, which is suggestive of cognitive disinhibition (Yao et al, 2010). Although the finding of reduced P3 for negative faces in negative priming condition can be related to previous work on reduced prefrontal control in depression (Canli et al, 2004), the use of ERP methodology does not allow us to give the exact localisation of the source of neural activation. However, functional neuroimaging and EEG studies point to abnormal anterior cingulate activity in depressed subjects during cognitive effort (George et al, 1997;Diener et al, 2009;Diener et al, 2010)..…”
Section: Discussionmentioning
confidence: 92%
“…In a recent first study combining the NAP task with ERP in MDD, it was also found that MDD participants had reduced central-parietal P2 amplitude for negative experimental trials, which is suggestive of cognitive disinhibition (Yao et al, 2010). Although the finding of reduced P3 for negative faces in negative priming condition can be related to previous work on reduced prefrontal control in depression (Canli et al, 2004), the use of ERP methodology does not allow us to give the exact localisation of the source of neural activation. However, functional neuroimaging and EEG studies point to abnormal anterior cingulate activity in depressed subjects during cognitive effort (George et al, 1997;Diener et al, 2009;Diener et al, 2010)..…”
Section: Discussionmentioning
confidence: 92%
“…In addition to such increased activation in the superior temporal gyrus in the active group during transfer run, our present results further show elevated resting-state connectivity between the pgACC and the superior temporal gyrus in the active group several days after neurofeedback training. Superior temporal regions are involved in emotional processing and social cognition (Allison et al, 2000;Gallagher and Frith, 2003;Olson et al, 2007), and are less active in MDD versus healthy individuals (Canli et al, 2004;Drevets et al, 2008;Fitzgerald et al, 2008). Therefore, the increased activity and connectivity in these regions in MDD patients suggests that this neurofeedback procedure effectively recruits other regions that are important in emotional regulation which show abnormal BOLD responses in MDD, further suggesting the potential for rtfMRI-nf in MDD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…George et al [28] and Miller et al [29] found the mid cingulate and the rACC to be especially sensitive for EST interference. Accordingly, increased activation in rostral and caudal parts of the ACC was found with variations of the standard EST [22,30,31]. While emotional interference in the traditional version of the EST is induced by stimuli with an emotional content (e.g.…”
Section: Introductionmentioning
confidence: 99%